Humic Silica for Optimising Soil Phosphorus Availability and Phosphorus Uptake by Maize Plants on Industrial Contaminated Lands - Diqy Ridwan Aditama; Wanti Mindari; Maroeto Maroeto; M Ghufron Chakim (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This study aimed to evaluate the effect of humic-silica application on P availability and P uptake by corn in land contaminated with heavy metals. The experiment was arranged in a Completely Randomized Design (CRD) with two treatment factors. The first factor consisted of three industrial locations: the pharmaceutical industry, the animal feed industry, and the paper industry. The second factor consisted of four levels of humic-silica application (in kg/ha): 0, 10, 20, and 30. Observations were made at the age of 14 and 70 days after planting (DAP). The parameters included soil organic carbon, Cation Exchange Capacity (CEC), soil P-available, and total P uptake by corn plants. Results showed that the humic-silica application at 20 kg/ha had a significant effect on P-available and P uptake by corn plants. This positive effect was consistent in the three industrial locations, both in 14 DAP and 70 DAP observations. These findings indicate that the use of humic-silica at 20 kg/ha has potential to reduce the negative impacts of heavy metal pollution on the availability of plant nutrients in industrial lands. This study provides insight into strategies for managing industrially contaminated lands to increase agricultural productivity, especially in terms of increasing the availability and absorption of phosphorus by corn plants.